A promising all-inorganic green-emitting YAGG:Ce phosphor-in-glass for laser lighting. Issue 18 (19th April 2022) - Wang, Luhan; Zhang, Jiangdan; Wang, Liansheng; Liang, Yueyuan; Xu, Fucai; Xu, Li; Liang, Xiaojuan; Chen, Qing; Xiang, Weidong
Abstract : The modular LD was packaged with a YAGG:Ce PiG prototype with bright green light observed, which provides a new possibility for long-term and stable LDs. Abstract : Phosphor-in-glass (PiG) as a reliable color converter has drawn considerable attention in solid-state laser lighting. Here, a series of green-emitting Y3 Al3.5 Ga1.5 O12 :Ce (YAGG:Ce) PiG samples are fabricated via a solid-state reaction method. The microstructure, photoluminescence and thermal performance of the YAGG:Ce PiG samples are systematically investigated. Impressively, the optimized sample not only exhibits a superior internal quantum efficiency of 94% but also has a remarkable thermal conductivity of 2.5 W m −1 K −1 . Moreover, it achieves excellent thermal stability (maintaining 81.2% of the room-temperature intensity at 473 K). Notably, the maximum luminous efficacy of the as-synthesized sample is 236.8 lm W −1 under a blue laser power density of 2.77 W mm −2 . Furthermore, a prototype laser diode packaged with the high efficiency and robust YAGG:Ce PiG produces bright green light, indicating its enormous potential as a green color converter for application in laser-driven lighting.